Persepsi Guru dan Peserta didik kelas XI IPA Terhadap Pembelajaran Online Selama Masa Pandemi Pada Mata Pelajaran Biologi di SMA Negeri 2 Sungai Penuh - Alfina Rahayu; Rahmadhani Fitri (Symbiotic: Journal of Biological Education and Science, 2021)
COVID-19 has an impact on various sectors of life. One of them has an impact on the education system. The learning system that is usually carried out directly and face-to-face has turned into online learning where teachers and students do not need to meet in person. Online learning is an alternative to break the chain of spreading COVID-19. Online learning is a new challenge for Indonesian education. One of them is learning biology. This research was conducted to determine the perceptions of teachers and students regarding online learning during the pandemic period in biology subjects. The method used was a survey by distributing questionnaires to teachers and students of class XI IPA as respondents. The questionnaire consists of several statement items using a Likert scale with 4 alternative answers. The questionnaire for teachers focuses on 4 dimensions, namely implementation, interest, motivation, and attitudes and responses. In the questionnaire for students, it focuses on 5 dimensions, namely implementation, interest, motivation, attitudes and responses, and satisfaction. The results showed that online learning in biology subjects had not been carried out well. Teachers and students have problems in implementing online biology learning